Effects of game design characteristics of a virtual reality serious game for upper-limb prosthesis control training on motor learning - Tchimino, Jack; Maas, Bart; van Dijk, Bram; Murgia, Alessio; van der Sluis, Corry K.; Bongers, Raoul M. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionRehabilitation outcomes of hand prosthesis control training generally benefit from an early start in the rehabilitation regimen as well as the use of modern technologies, like serious games, in lieu of more conventional methods. In this study, we tested a virtual reality based myoelectric prosthesis training serious game, specifically how the game design elements affected different aspects of motor control and training.MethodsTen able-bodied participants were asked to execute a series of tasks by controlling an LDA-controlled 1-DoF virtual hand prosthesis within a virtual reality environment (VRE) serious game. The tasks included grasping and manipulating virtual objects and controlled force modulation, the latter facilitated by artificial feedback communicated to participants in the VRE.ResultsThe results indicated that the game physics affected the way that the participants completed the tasks, while the tasks themselves appeared to be approached and executed in different ways by the participants. Contrary to expectations, however, the force feedback did not influence the participants' ability to precisely modulate the grasping force applied with the virtual prosthesis.DiscussionBased on these results, it can be concluded that users can be trained within the proposed framework to develop motor skills that might be translated into the use of a real prosthesis, in a more engaging and timely manner.